Antipsychotic utilization trajectories three years after initiating or reinitiating treatment of schizophrenia: A state sequence analysis approach. (22nd February 2022) - Brodeur, Sébastien; Vanasse, Alain; Courteau, Josiane; Courteau, Mireille; Stip, Emmanuel; Fleury, Marie‐Josée; Lesage, Alain; Demers, Marie‐France; Roy, Marc‐André
Abstract: Objective: This study aims to describe the utilization patterns of antipsychotic (AP) medication in patients with schizophrenia (SCZ), three years after initiating or reinitiating a given AP. Methods: Based on medico‐administrative information on patients living in Quebec (Canada), this retrospective cohort study included 6444 patients with a previous diagnosis of SCZ initiating or reinitiating AP medication between January 1, 2012, and December 31, 2014, with continuous coverage by public drug insurance. For each day of follow‐up (1092 days), patient was either exposed to one of the chosen categories of APs, or to none. This patient's sequence of AP exposure overtime has been referred to as the "antipsychotic utilization trajectory". These trajectories were analyzed using a State Sequence Analysis, an innovative approach which provides useful visual information on the continuation and discontinuation patterns of use over time. Results: Clozapine and long‐acting injectable second‐generation APs had the best continuation and discontinuation patterns over 3 years among all other groups, including less switching of APs, while oral first‐generation APs had the poorest patterns. These findings were comparable among incident and non‐incident cohorts. Oral second‐generation antipsychotics, excluding clozapine, had a poorer continuation and discontinuation pattern than long‐acting injectable antipsychotics. Conclusion: State Sequence Analysis provides a clear representation of treatment adherence in comparison with dichotomous indicators of adherence or discontinuation. Consequently, this innovative method has shed light on the impact of the AP chosen to initiate or reinitiate treatment in SCZ, which has been identified as a key factor for long‐term treatment continuation and discontinuation.